Pengaruh Latihan Pliometrik Depth Jump Terhadap Power Otot Tungkai Pada Pemain Bulutangkis Universitas Muhammadiyah Surakarta - Priambada, Tri Amanulah; , Maskun Pudjianto, S.MPh, M.Kes; , Totok Budi Santoso, S.Fis., MPH (2015)
Background:In badminton requires a huge leap to do a smash, it would require a good leg muscle power. Muscle power is one of the physical ability to use the maximum force in a short time. Many kinds of exercises to improve leg muscle power, one of them with depth jump plyometrics exercises. Plyometrics exercise is depth jumps leap repeatedly by jumping from the bench then landed, followed by jumping as high. The Objective of Research: To know effect of exercise plyometric depth jump to power players badminton leg muscle muhammadiyah university of surakarta. The Benefit of Research: Determine the effect exercises plyometrics depth jump to power players badminton leg muscle muhammadiyah university of surakarta. The Method of Research: This type of research in this study is a quasi experimental with pre and post test approach with control group design. The sampling technique is purposive sampling with inclusion and exclusion criteria. High-stepping measurement using vertical jump. The analysis in this wicoxon signed rank test and mann-whitney test, p value < 0,05 there is the influence or p value > 0,05 there is not the influence. Result of the Research: Statistical analysis of the results p value of 0,005, with a significant level of p<0.05, which means there is the influence of exercises plyometrics depth jump to power players badminton leg muscle muhammadiyah university of surakarta. Conclusion: there is the influence of exercises plyometrics depth jump to power players badminton leg muscle muhammadiyah university of surakarta.